Multilocus phylogeny and taxonomy of European Melanoleuca subgenus Melanoleuca - Antonín, Vladimír; Ďuriška, Ondrej; Jančovičová, Soňa; Para, Roberto; Kudláček, Tomáš; Tomšovský, Michal (Mycologia, 2022)
Revision of the taxonomically complicated European Melanoleuca taxa with well-developed macrocystidia (subgenus Melanoleuca) is presented. The species are delimited by macro- and micromorphological characters and by multilocus molecular data based on internal transcribed spacer (ITS), second largest subunit of RNA polymerase I (rpb2), and translation elongation factor 1-alpha (tef1) genes. The study is based on both type material and recent collections. Phylogenetically, these taxa form 10 clades recognized as 11 separate species: M. albomarginata, M. ammophila, M. bataillei, M. cavipes, M. friesii, M. granadensis, M. melaleuca, M. pallidicutis, M. polioleuca, M. strictipes, and M. variabilis. Three species, M. albomarginata, M. ammophila, and M. variabilis, are described as new. Melanoleuca melaleuca is discussed here as the type species of the genus. Discussion of other older names and their taxonomic status is also provided.
Keywords: DNA, Ribosomal Spacer; type revisions; RNA Polymerase I; 3 new species; zvířata; DNA sequencing; RNA-polymerasa I; 11 new typifications; Phylogeny; fylogeneze; systematics; mezerníky ribozomální DNA; Agaricomycetes; Animals